A Search For Variables That Affect School Climate in Hawaii - John A. Thompson; Sandra Young (Educational Considerations, 1992)
While climate is a somewhat global concept involving a generalized perception of a school by its publics, the question remains as to whether there are variables within the context which are related to, and may have some explanatory power in, determining climate scores.